Cadillac V-16s lost and found : tracing the histories of the 1930s classics - Cummings, Christopher W., 1952- (McFarland & Company, Inc., Publishers, 2014)
"For eleven years prior to World War II, Cadillac defied the norms of practicality and produced an extravagant supercar, a 16-cylinder luxury automobile that could be tailored to the customer's every want. Big, thirsty and lavish, it cemented Cadillac's place in the top tier of motoring magnificence"--